2021
DOI: 10.1007/s10342-021-01377-w
|View full text |Cite
|
Sign up to set email alerts
|

Modelling natural regeneration of European beech in Saxony, Germany: identifying factors influencing the occurrence and density of regeneration

Abstract: The potential utilisation of natural regeneration of European beech (Fagus sylvatica L.) for forest conversion has received little attention to date. Ecological knowledge is necessary to understand and predict successful natural regeneration of beech. The objective of this study was to improve understanding of what drives the occurrence of beech regeneration and, once regeneration is present, what drives its density. In the study, we utilised a forest inventory dataset provided by Sachsenforst, the state fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Although the Ellenberg theory is taken as given throughout research to date (e.g., Barna & Bosela, 2015;Mellert et al, 2016;Leuschner, 2020;Cailleret et al, 2020), only some elements of the theory have been confirmed. The predicted pattern of Fagus' predominance under mesic environmental conditions has been supported by numerous descriptions of natural forests (Peters, 1997;Leuschner et al, 2006;Bolte et al, 2007;Axer et al, 2021; but see minor modifications by Leuschner & Ellenberg, 2017b).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although the Ellenberg theory is taken as given throughout research to date (e.g., Barna & Bosela, 2015;Mellert et al, 2016;Leuschner, 2020;Cailleret et al, 2020), only some elements of the theory have been confirmed. The predicted pattern of Fagus' predominance under mesic environmental conditions has been supported by numerous descriptions of natural forests (Peters, 1997;Leuschner et al, 2006;Bolte et al, 2007;Axer et al, 2021; but see minor modifications by Leuschner & Ellenberg, 2017b).…”
Section: Introductionmentioning
confidence: 77%
“…Specifically, studies have shown physiological constraints on Fagus in highly acidic soil conditions (Leuschner et al, 2006;Aertsen et al, 2012), but not in calcareous soils (Ljungström et al, 1990). Also in wet, waterlogged soils, Fagus experiences reduced physiological functioning (Dreyer, 1994;Schmull & Thomas, 2000;Scharnweber et al, 2013;Axer et al, 2021), leading to increased adult mortality (Gorzelak et al, 2000). While Fagus is moderately drought-tolerant (Niinemets & Valladares, 2006;Rötzer et al, 2017;Leuschner, 2020), extreme drought conditions make saplings susceptible to embolism (Tomasella et al, 2019), reduce nitrogen uptake (Fotelli et al, 2001;Geßler et al, 2006;Leuschner, 2020), and inhibit adult growth (Ciais et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While our study focuses on a specific stand of Pinus canariensis in Tenerife, the methodology we employed provides a framework applicable to similar forest ecosystems. However, it is crucial to acknowledge the potential effect of other site-specific factors, such as topography, climate, and species traits, on the regeneration success [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…While beech regeneration is less frequent on temporarily waterlogged sites (Axer et al 2021a), no difference between welldrained sites and temporarily waterlogged sites can be demonstrated for oak regeneration (Tab. 1).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Information obtained from the plots are quadratic mean diameter (d q ), total basal area, tree species-specific basal areas, stand density index (SDI) and a spatially interpolated browsing percentage on rowan. For further information on the inventory design, please refer to Axer et al (2021a). Since seed dispersal also extends the radius of the plot (Kurek & Dobrowolska 2016), remote sensing data were incor-porated to determine distances to the nearest potential seed trees.…”
Section: Study Area and Inventory Designmentioning
confidence: 99%